Non-coding RNAs Regulate the Pathogenesis of Aortic Dissection - Hu, Yu-Yuan; Cheng, Xin-Meng; Wu, Nan; Tao, Yang; Wang, Xue-Ning (Frontiers in Cardiovascular Medicine, 2022)
Aortic dissection (AD) is a fatal cardiovascular disease. It is caused by a rupture of the aortic intima or bleeding of the aortic wall that leads to the separation of different aortic wall layers. Patients with untreated AD have a mortality rate of 1% to 2% per hour after symptom onset. Therefore, effective biomarkers and therapeutic targets are needed to reduce AD-associated mortality. With the development of molecular technology, researchers have begun to explore the pathogenesis of AD at gene and protein levels, and have made some progress, but the pathogenesis of AD remains unclear. Non-coding RNAs, such as microRNAs, lncRNAs, and circRNAs, have been identified as basic regulators of gene expression and are found to play a key role in the pathogenesis of AD. Thus, providing a theoretical basis for developing these non-coding RNAs as clinical biomarkers and new therapeutic targets for AD in the future. Previous studies on the pathogenesis of AD focused on miRNAs, but recently, there have been an increasing number of studies that explore the role of lncRNAs, and circRNAs in AD. This review summarizes the existing knowledge on the roles of various non-coding RNAs in the pathogenesis of AD, discusses their potential role as clinical biomarkers and therapeutic targets, states the limitations of existing evidence, and recommends future avenues of research on the pathogenesis of AD.